Origin of the response to adrenal and sex steroids: Roles of promiscuity and co-evolution of enzymes and steroid receptors. Issue 151 (July 2015) - Baker, Michael E.; Nelson, David R.; Studer, Romain A.
Highlights: Adrenal and sex steroid receptors first appear in an ancestral chordate. Cyclostome clade (lampreys and hagfish) contain an ER, PR and CR. There was multiple independent evolution of CYP11B2 in mammals. Abstract: Many responses to adrenal and sex steroids are mediated by receptors that belong to the nuclear receptor family of transcription factors. We investigated the co-evolution of these vertebrate steroid receptors and the enzymes that synthesize adrenal and sex steroids through data mining of genomes from cephalochordates [amphioxus], cyclostomes [lampreys, hagfish], chondrichthyes [sharks, rays, skates], actinopterygii [ray-finned fish], sarcopterygii [coelacanths, lungfishes and terrestrial vertebrates]. An ancestor of the estrogen receptor and 3-ketosteroid receptors evolved in amphioxus. A corticoid receptor and a progesterone receptor evolved in cyclostomes, and an androgen receptor evolved in gnathostomes. Amphioxus contains CYP11, CYP17, CYP19, 3β/Δ5–4-HSD and 17β-HSD14, which suffice for the synthesis of estradiol and Δ5-androstenediol. Amphioxus also contains CYP27, which catalyzes the synthesis of 27-hydroxy-cholesterol, another estrogen. Lamprey contains, in addition, CYP21, which catalyzes the synthesis of 11-deoxycortisol. Chondrichthyes contain, in addition, CYP11A, CYP11C, CYP17A1, CYP17A2. Coelacanth also contains CYP11C1, the current descendent from a common ancestor with modern land vertebrate CYP11B genes, which catalyze the synthesis of cortisol, corticosterone and aldosterone. Interestingly, CYP11B2, aldosterone synthase, evolved from separate gene duplications in at least old world monkeys and two suborders of rodents. Sciurognathi (including mice and rats) and Hystricomorpha (including guinea pigs). Thus, steroid receptors and steroidogenic enzymes co-evolved at key transitions in the evolution of vertebrates. Together, this suite of receptors and enzymes through their roles in transcriptional regulation of reproduction, development, homeostasis and the response to stress contributed to the evolutionary diversification of vertebrates. This article is part of a Special Issue entitled 'Steroid/Sterol signaling'.